Survey on SDN-based network testbeds - Tao HUANG; Jiang LIU; Chen ZHANG; Liang WEI; Yunjie LIU (Tongxin xuebao)
The network testbed based on software defined networking (referred as SDN testbed) has attracted extensive attention in the academic and industrial circles in recent years,and there have been many valuable cases of system/platform construction.Therefore,an overview of the SDN testbed was intended to conduct in the global scope.Firstly,the advantages of the SDN testbed and the basic design principles of the large-scale SDN testbed was explored comparing with the traditional network testbed.Secondly,in-depth analysis of existing SDN testbed projects was provided from the aspects of the project objectives and progress,the key technologies,network deployment,and featured applications.Finally,the challenges faced in this field were described in terms of network slicing,light and wireless convergence,security,and reliability.Future research directions are also suggested.